2019
DOI: 10.18845/tm.v32i7.4272
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição longitudinal de fertilizante granulado em diferentes inclinações e posição da rosca de um dosador de rosca helicoidal dupla

Abstract: A distribuição de fertilizante por dosadores de rosca helicoidal é um fator essencial para o estabelecimento e rendimento das culturas. O objetivo do trabalho foi mensurar a eficiência de um novo dosador de fertilizante de rosca dupla. O experimento foi realizado em bancada de teste com uma esteira (5.4 km h-1), empregando delineamento inteiramente casualisado. Foi usado dose fixa de 220kg ha-1, sendo que foram testadas 3 roscas (22mm, 17mm, e 34mm) trabalhando a 54 rpm. Cada teste era realizada coletas a cada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…According to Verardi et al (2019), the smaller the helical pitch, the higher the uniformity of fertilizer application on the row. When using meterings with two helicoids, the same authors found variations around 36% in the deposition of fertilizers in the application row.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Verardi et al (2019), the smaller the helical pitch, the higher the uniformity of fertilizer application on the row. When using meterings with two helicoids, the same authors found variations around 36% in the deposition of fertilizers in the application row.…”
Section: Resultsmentioning
confidence: 99%
“…Although the 10% variation is considered acceptable, variations in the fertilizer dose in the field exceed 40% (Weirich Neto et al, 2015;Rosa et al, 2019). The lack of fertilizer can reduce the yield (Weirich Neto et al, 2013), while overdose increases the risks of environmental degradation (Serrano et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations